The Islamic Military Alliance to Fight Terrorism: Structure, Mission, and Politics - Al-Ghalfi, Ali (Journal of Regional Security, 2018)
This paper is a preliminary examination of the newly established Islamic Military Alliance to Fight Terrorism (IMAFT). IMAFT’s membership includes Arab and Muslim states in the continents of Asia and Africa, and encompasses considerable military capabilities. The paper assumes that the advent of the Islamic Military Alliance is a significant event for both academic and empirical reasons, and employs insights gleaned from the International Relations literature on military alliances to analyse its structure, mission and politics. The discussion maintains that IMAFT sufficiently reflects the main conceptual aspects of military alliances, aims at performing vital collective security functions, and involves some of the immediate and potential issues typically associated with alliance politics. While the emerging alliance is yet to evolve towards institutionalised norms and procedures, the analysis shows that IMAFT is rel- evant for regional security politics and potentially conducive to addressing the growing global threat of terrorism.